LIGHT-EMITTING DIODE SOURCES OF LIGHTNING AS A SOURCE OF LOWERING COSTS OF SERVICE AND ENERGY CONSUMPTION OF TRAFFIC LIGHTS, HIGH LEVEL OF TRAFFIC MOVEMENT SAFETY - Rakhimberdiyevich, Normirzayev Abdukayum; Arslanovich, Eshanbabaev Abror; Nurmuhamedovna, Majidova Gulnoza; Abror ugli, Arslanov Jahongir (IJRDO - Journal of Mechanical And Civil Engineering, 2016)
Until recently in traffic lights ordinary glow lamps were used, but today on streets of the cities and railway routes the technological novelty – traffic lights light-emitting diode is strongly approved. Such replacement is caused them by their advantages. The applications of LED light sources for traffic lights regulating the movement – the major devices on automobile and railway routes. Clearness of signals, the increased reliability are guarantee of safety for equipment and people.